Manajemen Ketahanan Pangan di Kabupaten Parigi Moutong - Wahyuningsih, Annisa; Hamid, Abdul; Afandi, Muhammad (JPS: Journal of Publicness Studies, 2025)
This study aims to describe and analyze the management of food security in Parigi Moutong Regency, with a focus on efforts to stabilize rice availability and identify the challenges encountered in the process. The research is grounded in the management functions theory by George R. Terry which encompasses planning, organizing, actuating, and controlling and refers to Law No. 18 of 2012 as the legal foundation for food security in Indonesia. Food security, as defined by this law, is a condition in which food needs are fulfilled for the nation down to individuals, reflected in the availability of sufficient, safe, diverse, nutritious, equitable, and affordable food. A qualitative descriptive approach was used in this study. Data were collected through in-depth interviews with key informants from the Food Security Office, farmers, and the community, as well as field observations and documentation related to rice availability and distribution. The data were then analyzed qualitatively to provide a comprehensive and in-depth overview of food security management in Parigi Moutong Regency. The results indicate that food security management in Parigi Moutong Regency has been implemented through various programs, such as increasing production via agricultural intensification, improving irrigation infrastructure, providing superior seeds, and strengthening distribution systems. However, rice availability still fluctuates from year to year. The challenges faced include internal factors such as extreme climate change, pest and disease outbreaks, and limitations in human resources and budget. External factors include suboptimal distribution systems, changes in consumption patterns, and fluctuating market prices. The study highlights the importance of improved coordination among stakeholders, capacity building for farmers, and the development of effective information and monitoring systems as strategic efforts to enhance food security in the region.